PHBS dan Brain Gym Menuju PAUD Sehat di Kintamani - Putu Indah Lestari; Elizabeth Prima; Indah Pramita (Ilin Institute, 2020)
The purpose of the community partnership program at Kintamani Kindergarten was to increase partners' knowledge about healthy living, provide health facilities that support learning activities in schools and improve the health of students and teachers. The methods of these program were: 1) training and assistance in brushing teeth and washing hands according to WHO standards; 3) workshops, training and mentoring for a brain gym; and 4) monitoring and evaluating activities. PHBS activities, namely training on brushing teeth, showed an improvement of students' skills by 25% after being given training. Hand washing training activities provided an improvement of students' skills in carrying out hand washing movements according to the correct stages by 27.5%. The team facilitated partners with a sink for washing hands. Brain gym activities resulted in an improvement of 43.7% in teachers' knowledge and skills. The service team also provided a brain gym package consisting of 1 brain gym video CD, 1 guidebook, and 1 gym brain movement poster. It also showed that 88% of the teachers' responses stated that the partnership program activities had succeeded in increasing the knowledge and skills of partners. Overall, the results of the partner response questionnaire were 85.5% of PKM activities had a positive impact on partners.